Severity and Prognosis of Vascular Dementia in Patients with Acute Cerebral Infarction Combined with H-Type Hypertension and Its Correlation with Uric Acid Levels - Hong Y; Feng M (Neuropsychiatric Disease and Treatment)
Yang Hong,1 Min Feng2 1Graduate School of Bengbu Medical University, Bengbu, Anhui, 233030, People’s Republic of China; 2Department of Neurology, The Second Affiliated Hospital of Bengbu Medical University, Bengbu, Anhui, 233000, People’s Republic of ChinaCorrespondence: Min Feng, Department of Neurology, The Second Affiliated Hospital of Bengbu Medical University, No. 633 Longhua Road, Huaishang District, Bengbu, Anhui, 233000, People’s Republic of China, Tel +86-13855253675, Email fengmin0119@126.comAim: To investigate the correlation between serum uric acid levels and the severity and prognosis of acute cerebral infarction (ACI) combined with vascular dementia (VD) in patients with H-type hypertension.Methods: A retrospective analysis was conducted on 150 patients with VD after acute ischemic stroke (AIS) admitted to the Second Affiliated Hospital of Bengbu Medical College from September 2021 to March 2023. Patients with H-type hypertension (n=84) formed the observation group, while those without (n=66) formed the control group. Uric acid levels were compared between groups. Based on cognitive function scores, patients were further classified into mild, moderate, and severe dementia subgroups, and differences in uric acid and homocysteine levels were analyzed. Prognosis was assessed in the observation group after three months of treatment using activities of daily living scores, and logistic regression was performed to identify prognostic factors.Results: The observation group had significantly higher blood uric acid levels than the control group (P< 0.05). Within the observation group, uric acid and homocysteine levels differed significantly among dementia severity subgroups (P< 0.05) and were significantly higher than in the control group (P< 0.01). MMSE scores were negatively correlated with uric acid and homocysteine levels. Logistic regression analysis identified uric acid as an independent risk factor for prognosis.Conclusion: Elevated serum uric acid levels in patients with ACI and H-type hypertension are associated with greater dementia severity and poorer prognosis, highlighting the importance of monitoring uric acid levels in these patients.Keywords: acute ischemic stroke, vascular dementia, H-type hypertension, blood uric acid, blood homocysteine